1984
DOI: 10.1210/jcem-58-3-521
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Prolactin-Producing Cells from First and Second Trimester Decidua*

Abstract: Two cell types isolated and purified to homogeneity from human decidua obtained at 8-17 weeks of gestation were shown immunocytochemically to correspond to decidual and epithelial cells in the tissue of origin. The decidual cells reacted with antihuman PRL antiserum, and epithelial cells reacted with antiserum against keratin, an epithelial cell marker. Decidual and epithelial cells were cultured separately to determine their abilities to release PRL to the medium. Decidual cells released 140-410 ng PRL/mg pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Isolation of Decidual Cells-Decidual cells were isolated from human decidual tissue by limited enzymatic digestion and separation on Percoll gradients according to previously described methods (20). Cells were plated in plastic plates and allowed to replicate to confluence in primary monolayer culture.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation of Decidual Cells-Decidual cells were isolated from human decidual tissue by limited enzymatic digestion and separation on Percoll gradients according to previously described methods (20). Cells were plated in plastic plates and allowed to replicate to confluence in primary monolayer culture.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation at 1,200 g, the middle layer containing cytotrophoblasts was collected and washed. Decidual cells were isolated from decidual tissue dissected from placental membranes by the method ofBraverman et al (10). This procedure involved the digestion of decidual tissue with 0.25% collagenase A (Boehringer-Mannheim, Indianapolis, IN) at 37°C for 2 h followed by centrifugation through a 20-60% Percoll gradient.…”
Section: Methodsmentioning
confidence: 99%
“…This indicate that the specific hybridization signal for PRL was detected over the decidual cells. Immunocytochemical studies have shown that decidual cells are strongly immunoreactive against PRL antisera [10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown PRL immunoreactivity in the decidual cells [10][11][12][13][14][15][16], and in situ hybridization histochemistry (ISH) showed the localization of PRL mRNA in the decidual cells [16]. However, regional differences in PRL gene expression, such as in the decidua basalis, decidua parietalis and decidua capsularis, have not been clarified yet.…”
Section: Introductionmentioning
confidence: 99%